2017
DOI: 10.1177/2325967117s00165
|View full text |Cite
|
Sign up to set email alerts
|

Knee OUTcome Study: A Comparison of the Patient Perceived Outcome between High Tibial Osteotomy, Unicompartmental and Total Knee Arthroplasty for Medial Compartment Osteoarthitis in Men under age 55.

Abstract: Objectives:Managing medial compartment osteoarthritis (OA) in the younger male patient is challenging because these patients tend to be physically high demand. Traditionally, High Tibial Osteotomy (HTO) has been the favoured surgical option, but Total (TKA) and Unicompartmental (UKA) knee arthroplasty have been more recently utilized. Our aims were to compare patient reported outcome, revision and reoperation rates with these 3 procedures.Methods:Using our hospital data bases we retrieved the details of male p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Several studies have reported on long-term survival rates following HTO. 13,17,21,23 The 85.3% survival probability rate reported in our investigation following HTO at 10-year follow-up is within the 58% to 91.6% range reported in prior studies, supporting the long-term success of the operation in appropriately selected patients.…”
Section: **supporting
confidence: 86%
“…Several studies have reported on long-term survival rates following HTO. 13,17,21,23 The 85.3% survival probability rate reported in our investigation following HTO at 10-year follow-up is within the 58% to 91.6% range reported in prior studies, supporting the long-term success of the operation in appropriately selected patients.…”
Section: **supporting
confidence: 86%
“…Nineteen studies reported procedure-related complications. [9][10][11]13,14,19,21,23,24,[26][27][28][29]31,[36][37][38][39]41] Complications occurred at a significantly higher rate in the HTO group than in the UKA group (OR, 4.88, 95% CI: 2.92-6.86, I 2 = 20%, P < .00001; Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…One study included 38 OWHTO and 19 CWHTO, [25] and 1 study included 57 OWHTO and 36 Demo-HTO. [28] UKA protheses have been reported as fixed-bearing [9,11,13,14,19,20,23,25,26,[29][30][31][32] and mobile-bearing UKA [10,21,22,24,27,28,[33][34][35][36]38,39] in 13 and 12 studies, respectively, but 4 studies did not mention the UKA type. [18,37,40,41] Tables 1,2 show the details of the included studies, and Tables 3,4 show their quality.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 2 more Smart Citations